Urban developments in late antique and medieval Rome : revising the narrative of renewal - Kalas, Gregor; Dijk, Ann van (Social worlds of late antiquity and the early Middle Ages, 2021)
A narrative of decline punctuated by periods of renewal has long structured perceptions of Rome's late antique and medieval history. In their probing contributions to this volume, a multi-disciplinary group of scholars provides alternative approaches to understanding the period. Addressing developments in governance, ceremony, literature, art, music, clerical education and the city's very sense of its own identity, the essays examine how a variety of actors, from poets to popes, addressed the intermittent crises and shifting dynamics of these centuries with creative solutions that bolstered the city's resilience. Without denying that the past (both pre-Christian and Christian) always remained a powerful touchstone, the studies in this volume offer rich new insights into the myriad ways that Rome and Romans, between the fifth and the eleventh centuries, creatively assimilated the past in order to shape the future.